EDUCATIONAL INTERVENTION AND ITS EFFECT ON HEALTH MANAGEMENT PRACTICES IN ADULTS WITH DIABETES - CELINE MATHEW C. (The Journal of Research ANGRAU, 2026)
The present study aimed to assess the effectiveness of an educational intervention ondietary practices, lifestyle behaviors and glycemic control among diabetic patients. A structurededucational programme supported by a computer-based software package was implementedamong 33 diabetic patients in the experimental group, while 35 patients served as controls. Theintervention emphasized dietary modification, physical activity, medical monitoring and risk factorawareness. Results indicated that 12 out of 15 recommended dietary practices were significantlyadopted by the experimental group following intervention. Post-intervention, there was a markedincrease in the intake of green leafy vegetables, other vegetables, and fruits, along with areduction in the consumption of cereals, fats and fleshy foods. Significant improvements werealso observed in health management behaviors, including daily exercise, periodic blood glucosemonitoring, and regular physician visits (P